Pendekatan REALISME DALAM PEMBELAJARAN ABAD 21 : Pendekatan Filosofis terhadap Pembelajaran Berbasis Realitas - Marnita Marta; Muthia Sandra Riphasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the development and application of realism in twenty-first-century education through a systematic review of ten articles published between 2020 and 2025. The main problem addressed in this study is the absence of a comprehensive mapping of how realism is integrated into modern educational demands, particularly those involving technology, evidence-based teaching, and contemporary curriculum design. Using a thematic literature review approach, this study analyzes the philosophical foundations, instructional implementation, curriculum relevance, and methodological perspectives presented in the selected studies. The findings demonstrate that realism emphasizes empirical facts, direct observation, and the linkage of concepts to real-world contexts, where concrete experiences enhance students’ conceptual understanding (Hafidhi et al., 2024; Arianti et al., 2024). In curriculum development, realism ensures that learning content aligns with societal needs and objective realities (Adyputri & Ismail, 2025), while in evidence-based teaching, it strengthens instructional decision-making through the use of data and empirical observations (Brooks & Carter, 2023; Smith, 2021). Furthermore, the philosophical and methodological contributions of Archer (2020) and Lourie and McPhail (2024) highlight the continued relevance of realism as an analytical framework in educational research. Overall, this study concludes that realism provides a vital foundation for promoting authentic, contextual, and empirical learning that aligns with twenty-first-century competencies, while also offering direction for further research and the development of educational practices grounded in objective reality.